Rancang Bangun Website E-Marketing Untuk Meningkatkan Pemasaran UMKM Beebee Hidroponik - Suci Mutiara; Sushanty Saleh; Alan Bima Mismin (Politeknik Negeri Sriwijaya, 2023)
UMKM Beebee Hydroponics is an UMKM that operates in the agricultural sector and is located in Metro City, precisely in Tejosari Village. UMKM Beebee Hydroponics is actively developing the cultivation of various types of mint leaves which are then processed into various products, such as tea, catnip and essential oils. To compete in an increasingly competitive market, Beebee hydroponic MSMEs need to increase their marketing efforts. In this digital era, one of the best ways to reach a wider market is through e-marketing websites. The aim of creating this E-Marketing Website is not only to help Beebee Hydroponics MSMEs in promoting and marketing their products widely, but also to help Beebee Hydroponics MSMEs in recording products and transactions, as well as making it easier for shop customers to order products online. This E-Marketing website was designed using the waterfall method with PHP and MySQL programming languages. Software test results have been tested using the Black-Box Testing method. As a result, the Website menu button functions well and the website can be run intelligently on all devices. The results of this research are the Beebee Hydroponic MSME E-Marketing Website which can manage sales online.